Research and Development of Technology for the Extraction Copper, Iron and Other Precious Metals from Copper Slag (Journal of Pharmaceutical Negative Results, 2022)
Copper slag was subjected to in-depth mineralogical characterization by integrated instrumental techniques and evaluated for the efficacy of physical beneficiation. In this study, a new technology has been developed to improve the enrichment of copper and iron components from copper slag, which promotes the mineralization of valuable minerals by modifying molten slag and promotes the growth of mineral grains. The results show that under appropriate conditions, the copper content of copper concentrate increased from 6.43% to 11.04%, the iron recovery of magnetic separation increased significantly from 32.40% to 63.26%, and other evaluation indicators slightly modified relative to unaltered copper slag.